About The Books That Children Need for Independent Reading in Addition to Textbooks, Which Are Necessary for Independent Thinking - Ismailova Lobar Maksudovna (Genius Journals, 2023)
A child's speech is formed at the stage of preparation for school education at the level of hearing and correct understanding of people's thoughts by communicating with adults. He can understand information about what he hears and sees. He knows how to present the information he has in a certain order, he uses mental operations appropriately. It will be discussed about the books that children need for independent reading in addition to textbooks, which are necessary for independent thinking
Keywords: Independent reading; information; school education; horizon